Youth at risk: politics, crime; its accessories and youth justice in South Africa - Choritz, Sharon Lisa (Democratic Governance and Rights Unit, 2023)
Youth violence assumes several forms which may be attributed towards a complex set of causes inextricably linked to the oppressive past which provide an explanation towards the nature and frequency of violence incidents. Central to such causes are; the 'culture of violence' which remains firmly entrenched in our society, structural inequalities onset by the Apartheid government and the escalating unemployment rates. Discourse intent upon providing explanations for the rising crime rates have emphasized unequal power relations, strong patriarchal values and entrenched conventional notions of masculinity and femininity as causal factors. The emphasis rests upon the fact that youth violence and victimization result not only from political and socioeconomic inequality, but may also be accredited towards expressions of gender identity as well as the manner in which society construct and reconstruct such identities. Dominant theorists' upon this subject, reason that poor, young men associate marginalization and powerlessness experienced under the Apartheid and post-Apartheid regime as a form of emasculation, which when internalized, finds its expression through the medium of violence. The alliance between male identity and criminal violence is expressed in crimes such as hijackings, assaults, gang activities, housebreakings and sexual violence committed against women and girls. Assessments of both national and international literature upon the subject of crime, delinquency and violence amongst youth have evolved along gender-specific lines. The general consensuses amongst researchers are that males both perpetrate and experience the most degree of violence and that this is generally recognized as a resulting effect of masculinity. The persistent popularity of violent crime in South Africa constitutes a form of 'compensatory manhood ' which witness young men searching to salvage a sense of masculinity/male identity by partaking in crime and violence. However, whilst it is imperative for the growth of this nation to recognize the contributing factors underlying the reasons as to why adolescents, especially males, gravitate towards subcultures, such as gangs, it is, nonetheless, imperative that such youngsters are restrained and their behaviour restricted as the violence of the Apartheid years has led to the belief among many South Africans that violence is an acceptable means of resolving conflict. The mistreatment of our youth under the Apartheid regime is a strong indicator that the South African justice system was not implemented with young people in mind and did not function with the purpose of assuming their fidelity. The reason in part, is our inheritance of a legal system, derived from Britain, which was designed for control, not for social restoration or personal transformation. Owing to the British influence upon our law, we too adopted such approach, though it was to our detriment. Furthermore, collective adolescent behaviour particularly in the arena of gangs is little understood by law officials skilled in western legal procedures. Thus, in dealing with youth at risk it is vital that one interacts with them in a fitting and fair manner as well as a suitable forum; subscribing to the fact that we too, experienced the anxieties and turmoil accompanied by the transition to adolescence and all that it presented namely; the pressures to conform and the wish to transform. Thus with this in mind, legal personnel, assume a responsibility by virtue of their title, to ensure inhabitants' of South Africa are dealt with in a manner particular to them. The central feature of this study was to explore the affiliation between marginalized youth, the construct of masculinity and its accompanying violence exhibited in South Africa today. This paper further serves to highlight the link between Apartheid, poverty, unemployment, unequal opportunities, gangs and crime and through the medium of this interrelated relationship; demonstrate how the effects of the past have impacted upon the opportunities for youth today.